DEM-Based Simulation Study on the Operational Performance of a Single Horizontal Shaft Forced-Action Mixer - Haipeng Yang; Guanguo Ma; Wei Zhao (Buildings)
This study conducts a numerical simulation of the working performance of a single horizontal shaft forced mixer using the Discrete Element Method (DEM). It systematically investigates the effects of blade installation angle, feeding method, mixing speed, and coarse aggregate particle size on the mixing uniformity. A 1:2 scale model was developed, incorporating Newton’s laws of motion and a soft-sphere contact model to simulate the particle trajectories and interactions during mixing. The results indicate that top–bottom feeding enhances mixing efficiency significantly by forming vertical convective circulation, achieving a mixing uniformity above 0.9. A moderate rotation speed of 30 rpm provides the best balance between energy consumption and mixing performance. As the coarse aggregate size increases (from 9 mm to 15 mm), the enhanced particle inertia leads to a decrease in mixing uniformity (from 0.9 to 0.6). Additionally, the discrepancy between simulation and experimental results is less than 0.1, validating the reliability of the model. This research offers theoretical guidance for the structural optimization and parameter selection of single-shaft mixers, contributing to improved mixing efficiency and concrete quality in engineering applications.